Figure sculpture in wax and plaster - Miller, Richard McDermott 1922- (New York Dover Publications, Inc., 1971)
"The author describes how to work with wax: modifying waxes, controlling temperature, cooling, heating, cutting, and modeling wax"--Book jacket.
Includes index.
Keywords: Figure sculpture -- Technique; Plaster sculpture -- Technique; Wax-modeling -- Technique